Computational modelling vs. Computational explanation: Is everything a Turing Machine, and does it matter to the philosophy of mind? - Piccinini, Gualtiero (Australasian Journal of Philosophy, 2007)
According to pancomputationalism, everything is a computing system. In this paper, I distinguish between different varieties of pancomputationalism. I find that although some varieties are more plausible than others, only the strongest variety is relevant to the philosophy of mind, but only the most trivial varieties are true. As a side effect of this exercise, I offer a clarified distinction between computational modelling and computational explanation.